Les nouvelles monnaies numériques : au-delà de la dématérialisation de la monnaie et de la contestation des banques - Alain Laurent; Virginie Monvoisin (Revue de la Régulation)
New digital moneys are spreading. Mobil moneys and other cyber moneys merge everywhere in the world and arouse an unexperienced interest. In the early 2000s, there were no more academic controversies, but with new monetary instruments new questions and analyses come to the fore. The hierarchical banking system is facing this new phenomena and the payment system that we are used to is at stake. Moreover, new agents and new digital moneys challenge the common view of money in an attempt to emancipate from monetary and banking institutions. It is necessary to resort to monetary theory in order to clarify the nature of new instruments: are they money, do they represent a new form of money or is the plurality of money at stake?